A Meta-Analysis of Applications of Diffusion Models - Sultan, Fareena; Farley, John U.; Lehmann, Donald R. (Journal of Marketing Research, 1990)
A meta-analysis of 213 applications of diffusion models from 15 articles relates model parameters to the nature of the innovation, the country under study, model specification, and estimation procedure. The effect of use of the same data by several researchers is examined, as are weighting schemes for improving efficiency of the meta-analysis. A Bayesian scheme is used to combine results from the metaanalysis with new data for estimation of parameters in a new situation.